2017
DOI: 10.1038/eye.2017.249
|View full text |Cite
|
Sign up to set email alerts
|

Gun trauma and ophthalmic outcomes

Abstract: PurposeThis retrospective cohort study assesses the visual outcomes of patients who survive gunshot wounds to the head.MethodsThe Elmhurst City Hospital Trauma Registry and Mount Sinai Data Warehouse were queried for gun trauma resulting in ocular injury over a 16-year period. Thirty-one patients over 16 years of age were found who suffered a gunshot wound to the head and resultant ocular trauma: orbital fracture, ruptured globe, foreign body, or optic nerve injury. Gun types included all firearms and air guns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…200,201 Limited data are available on the long-term visual outcomes of ocular trauma, but it is estimated that FAOI results in permanent visual loss in 44% of cases. 202 One study demonstrated that Black patients represent the majority of patients who undergo enucleation or evisceration after severe ocular trauma. 197 Furthermore, the average age at eye removal is also younger among Black and Hispanic patients than among White patients.…”
Section: Epidemiology Of Disparities By Eye Diseasementioning
confidence: 99%
“…200,201 Limited data are available on the long-term visual outcomes of ocular trauma, but it is estimated that FAOI results in permanent visual loss in 44% of cases. 202 One study demonstrated that Black patients represent the majority of patients who undergo enucleation or evisceration after severe ocular trauma. 197 Furthermore, the average age at eye removal is also younger among Black and Hispanic patients than among White patients.…”
Section: Epidemiology Of Disparities By Eye Diseasementioning
confidence: 99%
“…According to the quality assessment of papers, 15 studies ( 24 – 27 , 29 , 30 – 35 , 39 , 45 ,, 48 , 51 ) were considered as “high quality”; 10 studies ( 23 , 28 , 36 38 , 40 43 , 52 ) were assigned as “fair to good quality”, and 5 studies ( 44 , 46 , 47 , 49 , 50 ) were regarded as low quality.…”
Section: Resultsmentioning
confidence: 99%
“…Most registries evaluated also used terminologies and International Classification of Diseases System (Ocular Trauma Score, Birmingham Eye Trauma Terminology) to name, define and classify eye injuries ( 24 – 27 , 31 , 32 , 34 , 36 , 39 , 43 , 44 , 49 , 50 ) while only four registries have used the International Classification of Diseases Ninth Revision (ICD-9) coding systems. The International Classification of Diseases (ICD-10)) was used for classifying variety of injuries, medical interventions and treatments for eye injuries ( 30 , 31 , 33 , 37 , 40 ). The minimum data sets in the studied registries were classified into 12 data classes.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible cause of limited reports about GSOI and visual results could arise from accompanying serious brain injury and neurologic complications, limiting the degree of ocular testing that can be performed. A 2018 study about ocular gunshot trauma and ophthalmic outcomes reported that 44% of patients (8 of 18) suffered from long-term visual damage 3. Of the 915 victims of gun trauma to the head described, 27 (3.0%) sustained ocular injuries but only 18 (67%) individuals survived 3.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 study about ocular gunshot trauma and ophthalmic outcomes reported that 44% of patients (8 of 18) suffered from long-term visual damage 3. Of the 915 victims of gun trauma to the head described, 27 (3.0%) sustained ocular injuries but only 18 (67%) individuals survived 3. The authors found that neither the location of injury nor the type of gun used predicted visual loss outcome.…”
Section: Discussionmentioning
confidence: 99%